Analisis Pertumbuhan dan Produksi Pisang Kepok Kuning Pada Dua Lokasi Tanah Di Desa Samberah Kecamatan Muara Badak Kabupaten Kutai Kartanegara: Analysis of Growth and Production of Kepok Kuning Banana in Two Soil Locations in Samberah Village, Muara Badak District, Kutai Kartanegara Regency - rustam baraq noor (Universitas Widya Gama Mahakam, 2020)
ABSTRACT Soil fertility in banana cultivation varies and this is what makes Kepok banana production very dependent on it. Banana plants planted in new cleared land originating from the forest are very fertile and are very different from other former crops or bananas. Planting locations in hilly areas away from nutrient-carrying rivers are the last resort due to limited land. This study aims to determine the level of soil fertility on the growth and production of yellow Kepok banana in Samberah, Batu-Batu village, Muara Badak district, Kutai Kartanegara district. Implementation for four months from April to July 2020. The research design used a completely randomized design (CRD) repeated ten times. Fertility levels include former rice fields and former banana plant lands. The results showed that the land formerly planted with bananas was significantly different from the former land planted with rice in the circumference parameter. There was a tendency for the dominance of high parameter data, the number of tillers, and production on former banana plantations. Kepok Kuning banana plants do not choose the location of the land. So that the cultivation of yellow Kepok banana plants can be planted on former banana plantations sustainably.